Servant Leadership and Organizational Commitment: A Comparative Study between Employees of Local and Foreign Bank in the Northern Region of Malaysia - Desa, Nasina Mat; Asaari, Muhammad Hasmi Abu Hassan; Mohamed, Baderisang (Scholars Middle East Publishers, 2018)
This study intends to examine the relationship and impact between servant leadership and organizational commitment in the context of bank employees. Moreover, it intends to discover the differences between bank employees who are working in the local and foreign banks in the Northern Region of Malaysia. Questionnaires had been distributed among bankers in local and foreign banks in the states of the Northern States of Malaysia, namely Penang, Perak, and Kedah. Almost 300 questionnaires were distributed. This paper adapted servant leadership instrument from Van Dierendonck and Nuijten. Furthermore, the organizational commitment had been adopted from Meyer and Allen. The study provide a better understanding of the right leadership in fostering employees commitment, improve the leader-follower relationship and allow more leaders to realize the benefits of using servant leadership in increasing their relationship with their subordinates, influencing the subordinates’ positive job behavior as well as increasing their subordinates’ satisfaction and commitment with their job, department, and organization. Furthermore, this study urges the human resource department to conduct proper leadership training to their employees to promote new ideas toward servant leadership to improve the leadership skills among bank employees that may lead to rising up their organizational commitment.